PENGEMBANGAN PETUNJUK PRAKTIKUM BERBASIS MEDIA 3D PAGEFLIP PROFESSIONAL MATERI ASAM DAN BASA - Nurul Hikmah; Rini Muharini; Rody Putra Sartika; Hairida hairida; Ira Lestari (Jurnal Education and Development, 2023)
This study aims to determine the feasibility of Pageflip 3D media-based practicum instructions on acids and bases, based on the results of expert tests and teacher responses. The form of this research is research and development (R&D) which adopts the ADDIE development model. The subject of this study was a practical guide based on Pageflip 3D media on acid and base materials which were tested for responses to 6 teachers who assisted all class XI teachers at SMA Negeri 1 Sungai Kakap. The data collection instruments used were feasibility assessment sheets and teacher response questionnaires. The results of data processing show that the practical instructions based on 3D Pageflip media developed are very suitable for use in practicum in terms of the percentage of material on the eligibility aspect of the content of 87.40% and the presentation aspect of 89.32%, the percentage of linguistics is 91.10% and the percentage of eligibility media is 82.58 %. Based on the calculation results, the percentage of teacher response questionnaires is 84.85%. The teacher's response to practical instructions based on 3D Pageflip media is classified as very high.